IMPACT OF SAIBA USERS, ACCOUNTING TRAINER, ORGANIZATIONAL CULTURE ON THE ADOPTIONS OF ACCRUAL BASED - Muh Sajjaj Sudirman (Jurnal Ilmiah Akuntansi Peradaban, 2022)
The goal of this study is to investigate the factors that influence the adoption of accounting-based accounting. The provincial office of South Sulawesi's Ministry of Religion provided the information used in this study. This study aims to objectively investigate the impact of organizational culture, accounting training, and the usage of SAIBA applications on the adoption of accrual based accounting in producing high-quality financial reports. The study's population consisted of 92 SAIBA application operators who worked in the South Sulawesi Regional Office of the Ministry of Religion. SPSS is the method used for data analysis. The findings of the study demonstrate that users, accounting training, and organizational culture all have a positive and significant impact on the adoption of accrual based. Keyword: SAIBA Users, Accounting Training, Organizational Culture, Accrual Based Accounting.